運算式 14: "x" Superscript, "x" , Baseline natural log left parenthesis, "x" , right parenthesis minus "x" "x" Superscript, left parenthesis, "x" minus 1 , right parenthesis , Baseline equals 0xxlnx−xxx−1=0
14
2. Substitute y=x
15
運算式 16:
16
運算式 17: "x" Superscript, "x" , Baseline natural log left parenthesis, "x" , right parenthesis minus "x" Superscript, "x" , Baseline equals 0xxlnx−xx=0
17
3. Simplify
18
運算式 19:
19
運算式 20: natural log left parenthesis, "x" , right parenthesis minus 1 equals 0lnx−1=0
20
4. Divide by x^x, because x can't be 0.
21
運算式 22:
22
運算式 23: natural log left parenthesis, "x" , right parenthesis equals 1lnx=1
23
運算式 24: "x" equals "e"x=e
24
Add 1 and solve.
25
運算式 26:
26
運算式 27: "x" equals "y" equals "e"x=y=e
27
x=y, so y also equals e. This means the intersection is at (e,e)